2014
DOI: 10.5194/soild-1-803-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amino acid and N mineralization dynamics in heathland soil after long-term warming and repetitive drought

Abstract: Abstract. Monomeric organic nitrogen (N) such as free amino acids (fAA) is an important resource for both plants and soil microorganisms and is, furthermore, a source of ammonium (NH4+) via microbial fAA mineralization. We compared gross fAA dynamics with gross N mineralization in a Dutch heathland soil using 15N labelling. A special focus was made on the effects of climate change factors warming and drought, followed by rewetting. Our aims were to: (1) compare fAA mineralization (NH4+ production from fAAs) wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…In contrast to our hypothesis, we did not find any significant effect of climatic treatments or vegetation type on gross N transformations (Supplementary Table 2). This is in line with the generally small changes in plant growth in the TasFACE experiment (Hovenden et al 2014), which did consequently not Similar to our results, gross N mineralization was unaffected by warming in a Dutch heathland (Andresen et al 2015). On the other hand, both increased (Larsen et al 2011;Björsne et al 2014) and decreased (Jamieson et al 1998;Niboyet et al 2011) gross N mineralization under warming has been reported.…”
Section: Resultssupporting
confidence: 90%
“…In contrast to our hypothesis, we did not find any significant effect of climatic treatments or vegetation type on gross N transformations (Supplementary Table 2). This is in line with the generally small changes in plant growth in the TasFACE experiment (Hovenden et al 2014), which did consequently not Similar to our results, gross N mineralization was unaffected by warming in a Dutch heathland (Andresen et al 2015). On the other hand, both increased (Larsen et al 2011;Björsne et al 2014) and decreased (Jamieson et al 1998;Niboyet et al 2011) gross N mineralization under warming has been reported.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, 1 mL deionized water was slowly added dropwise to each soil one day before labelling. The two 15 N labels were: 1. a 20 amino acids-mixture (AA; 'cell free powder' from Cambridge isotope laboratories; see (Andresen et al 2015)) with 99% 15 N, dissolved in 0.1 MolÁL -1 HCl, containing 0.36 g AA L -1 corresponding to 3 lg AA-N g -1 soil. ; and 2. ammonium sulphate with 99.8% 15 N, amended at a rate of 2 lg N g -1 soil.…”
Section: Nitrogen Turnover Rates By Pool Dilution Techniquementioning
confidence: 99%
“…The method to assess the individual free amino acid (FAA) content and isotopic enrichment is described in detail elsewhere Andresen et al 2015Andresen et al , 2016a. In short, at arrival at ISOFYS lab, the SPE columns were washed with 10 mL of ultrapure water after which the FAAs were eluted with 30 mL 3 MolÁL -1 NH 4 OH.…”
Section: Abundance and Isotopic Composition Of Individual Amino Acid mentioning
confidence: 99%
“…Depolymerization of proteinaceous organic material is an important pathway for generating bioavailable N in wide range of systems including boreal forests and is often considered a fungal trait (5, 7, 20, 22, 26-28). Depolymerization decomposes polymeric organic material into monomers and amino acids that can be used as C and N sources by soil microorganisms and plants (19, 20, 22, 29, 30).…”
Section: Introductionmentioning
confidence: 99%